Contribution of smoking to socioeconomic inequalities in mortality: a study of 14 European countries, 1990–2004. Issue 3 (27th April 2016) - Gregoraci, G; van Lenthe, F J; Artnik, B; Bopp, M; Deboosere, P; Kovács, K; Looman, C W N; Martikainen, P; Menvielle, G; Peters, F; Wojtyniak, B; de Gelder, R; et al.
Abstract : Background: Smoking contributes to socioeconomic inequalities in mortality, but the extent to which this contribution has changed over time and driven widening or narrowing inequalities in total mortality remains unknown. We studied socioeconomic inequalities in smoking-attributable mortality and their contribution to inequalities in total mortality in 1990–1994 and 2000–2004 in 14 European countries. Methods: We collected, harmonised and standardised population-wide data on all-cause and lung-cancer mortality by age, gender, educational and occupational level in 14 European populations in 1990–1994 and 2000–2004. Smoking-attributable mortality was indirectly estimated using the Preston-Glei-Wilmoth method. Results: In 2000–2004, smoking-attributable mortality was higher in lower socioeconomic groups in all countries among men, and in all countries except Spain, Italy and Slovenia, among women, and the contribution of smoking to socioeconomic inequalities in mortality varied between 19% and 55% among men, and between −1% and 56% among women. Since 1990–1994, absolute inequalities in smoking-attributable mortality and the contribution of smoking to inequalities in total mortality have decreased in most countries among men, but increased among women. Conclusions: In many European countries, smoking has become less important as a determinant of socioeconomic inequalities in mortality among men, but not among women. Inequalities in smoking remain one of the most important entry points for reducing inequalities in mortality.